2006
DOI: 10.1140/epjb/e2006-00191-0
|View full text |Cite
|
Sign up to set email alerts
|

Breather trapping and breather transmission in a DNA model with an interface

Abstract: We study the dynamics of moving discrete breathers in an interfaced piecewise DNA molecule. This is a DNA chain in which all the base pairs are identical and there exists an interface such that the base pairs dipole moments at each side are oriented in opposite directions. The Hamiltonian of the Peyrard-Bishop model is augmented with a term that includes the dipole-dipole coupling between base pairs. Numerical simulations show the existence of two dynamical regimes. If the translational kinetic energy of a mov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
1
13
0
4
Order By: Relevance
“…To obtain MBs, each breather should be perturbed using the initial conditions given by Eqs. (4). To obtain nonsymmetric collisions each perturbation must be different.…”
Section: Nonsymmetric Moving Breather Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain MBs, each breather should be perturbed using the initial conditions given by Eqs. (4). To obtain nonsymmetric collisions each perturbation must be different.…”
Section: Nonsymmetric Moving Breather Collisionsmentioning
confidence: 99%
“…Some studies about the existence and properties of MBs in the Peyrard-Bishop model including dipole-dipole dispersive interaction are carried out in [11] [4].…”
mentioning
confidence: 99%
“…The method used for calculating discrete breathers in (KG) lattices consists on approximating the dynamical equations by a Nonlinear Schrodinger Equation (NLS) and moving the breather by an envelope solution 17 . Cuevas, Palmero, Romero and Archilla have found that the moving breather can cross the impurity, and can be reflected by it, or can be trapped 18,19 . The problem is to determine the parameters of the model to generate a trapped breather (TB) which is very important for the DNA transcription.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the double strand corresponds to a Klein-Gordon chain, the variable parameters are the distances between nucleotides within each base pair, and only short-range interactions are considered because of the stacking coupling [17]. It is well known that the Peyrard-Bishop (PB) model can produce solitons due to the balanced competition between dispersion and nonlinear effects [18][19][20]. For example, in the continuum limit, nonlinear equations of motion for the system reduce to a pair of sine-Gordon-type equations, which have kink soliton solutions [21].…”
Section: Introductionmentioning
confidence: 99%